Color : a photographer's guide to directing the eye, creating visual depth, and conveying emotion - Foster, Jerod (Peachpit Press, 2014)
Approaches color from a photographer's perspective with a mix of practical theory, technical information, and solid advice on how to apply these details in all genres of photography--landscapes, portraits, lifestyle, sports, or wildlife. You will learn about: color in the frame, including guiding the eye and composing with color; manipulating color with white balance, artificial lighting, and exposure; creating visual depth with complementary colors, dominant/recessive colors, and contrast; the meaning of color and how red, blue, green or purple can push emotions; conditions for shooting color and the best times of day, and best practices for handling color in post processing.